THE EFFECT OF COMPETITIVE EXERCISES ON DEVELOPING CERTAIN PHYSICAL AND SKILL ABILITIES OF YOUNG GOALKEEPERS IN FOOTBALL - Radi, Safaa Kadhem (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2024)
This study aims to investigate the effect of competitive exercises on developing certain physical and skill abilities of young football goalkeepers. The researcher utilized the experimental method with an equivalent groups design. The research population consisted of young goalkeepers from clubs in Al-Diwaniyah province participating in the Iraqi youth football league, organized by the local football federation under the supervision of the Iraqi Central Football Federation. A total sample of 20 youth goalkeepers was randomly selected. The sample was divided into two groups: an experimental group and a control group, with 10 goalkeepers in each group, selected using a simple lottery method. The researcher ensured homogeneity and equivalence across the variables studied. The training program lasted six weeks, with three training sessions per week. Statistical analyses were conducted using the SPSS software package.